Juvenile arthritis management in less resourced countries (JAMLess): consensus recommendations from the Cradle of Humankind - Scott, Christiaan; Chan, Mercedes; Slamang, Waheba; Okong'o, Lawrence; Petty, Ross; Laxer, Ronald M.; Katsicas, Maria-Martha; Fredrick, Francis; Chipeta, James; Faller, Gail; Pileggi, Gecilmara; Saad-Magalhaes, Claudia [UNESP]; et al. (Springer, 2019)
Juvenile idiopathic arthritis (JIA) is the most prevalent chronic rheumatic disease in children and young people (CYP) and a major cause of pain and disability. The vast majority of the world's children and their families live in less resourced countries (LRCs) and face significant socioeconomic and healthcare challenges. Current recommendations for standards of care and treatment for children with JIA do not consider children living in less resourced countries. In order to develop appropriate recommendations for the care of CYP with JIA in less resourced countries a meeting of experienced pediatric rheumatologists from less resourced countries was convened with additional input from a steering group of international pediatric rheumatologists with experience in developing recommendations and standards of care for JIA. Following a needs assessment survey of healthcare workers caring for CYP with JIA in LRC, a literature review was carried out and management recommendations formulated using Delphi technique and a final consensus conference. Responses from the needs assessment were received from 121/483 (25%) practitioners from 25/49 (51%) less resourced countries. From these responses, the initial 84 recommendations were refined and expanded through a series of 3 online Delphi rounds. A final list of 90 recommendations was proposed for evaluation. Evidence for each statement was reviewed, graded, and presented to the consensus group. The degree of consensus, level of agreement, and level of evidence for these recommendations are reported. Recommendations arrived at by consensus for CYP with JIA in less resourced countries cover 5 themes: (1) diagnosis, (2) referral and monitoring, (3) education and training, (4) advocacy and networks, and (5) research. Thirty-five statements were drafted. All but one statement achieved 100% consensus. The body of published evidence was small and the quality of evidence available for critical appraisal was low. Our recommendations offer novel insights and present consensus-based strategies for the management of JIA in less resourced countries. The emphasis on communicable and endemic diseases influencing the diagnosis and treatment of JIA serves as a valuable addition to existing JIA guidelines. With increasing globalization, these recommendations as a whole provide educational and clinical utility for clinicians worldwide. The low evidence base for our recommendations reflects a shortage of research specific to less resourced countries and serves as an impetus for further inquiry towards optimizing care for children with JIA around the world.
Keywords: Developing world; Juvenile idiopathic arthritis; Management; Recommendations